Does cell wall integrity in legumes flours modulate physiochemical quality and in vitro starch hydrolysis of gluten-free bread?. (August 2019) - Boukid, Fatma; Vittadini, Elena; Lusuardi, Federica; Ganino, Tommaso; Carini, Eleonora; Morreale, Federico; Pellegrini, Nicoletta
Graphical abstract: Highlights: Intact and fractured cells were identified in legumes using optical microscope. Legumes flour properties were affected by cell wall structure. Cell wall intactness enhanced color and decreased firmness of gluten free bread. Intact cell walls significantly reduced the starch hydrolysis in gluten free bread. Abstract: Cell integrity has recently been recognized being a key factor in modulating nutrients accessibility, but it has not been assessed in the application of legumes flours in complex matrices. In this study, cell wall intactness [fractured cells (FC) or intact cells (IC)] and particle size significantly influenced the functional properties of legumes flours. Cannellini bean (CB) flour rich in IC was characterized by high water holding capacity and low starch gelatinization enthalpy, which are features appreciated in gluten-free (GF) bread. Regardless of cell structure, adding 20% of CB to a GF bread decreased breadcrumb hardness and increased crust yellowness. Bread made with IC was softer than that with unfractionated flour, FC and 100% rice. Noteworthy, the extent of starch hydrolysis was reduced when IC (≈33%) was used followed by unfractionated flour (≈40%), FC (≈46%) and 100% rice (≈64%). Predominance of IC enabled a natural barrier against amylolytic enzymes.